Removal of Pb2+ and Cd2+ from Aqueous Solutions using POCl3 Cross-linked Carboxymethyl Derivatives of Legume Starch - Akinterinwa, Ayodele; Oladele, Ebun; Adebayo, Albert; Ajayi, Olubode (UI Scholars Hub, 2020)
Starch was extracted from Kwakil beans and cross-linked with POCl3 (1% v/w of starch dry basis [db]). The cross-linked starch (PCS) derivative was carboxymethylated with sodium monochloroacetate (5% to 30% w/w of starch db) to obtain cross-linked carboxymethyl starch (PCCS) derivatives. The derivatives were used in the adsorption of Pb2+ and Cd2+, and the process was monitored using atomic adsorption spectrometer. Carboxymethylation enhanced adsorption of ions (Cd2+, 95% to 96%; Pb, 65% to 94%), and it was more appreciable with Pb2+ than Cd2+ as degree of substitution increased from 0.008 to 0.052. This was attributed to selective ion exchange, steric and stereochemical effects of the carboxymethyl groups. Derivatives were characterized with Fourier transform infrared spectroscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. Adsorption increased with pH and adsorbent dosage but decreased when temperature and interfering ion (i.e., Na+ and Ca2+) concentrations increased. Adsorption equilibrium was reached in 5 min. Kinetic parameters of Pb2+ fitted the pseudo-second-order model (R2 = 0.9999), while Cd2+ fitted the pseudo-first-order model (R2 = 0.9978). Isotherm parameters of Pb2+ fitted Langmuir model (R2 = 0.9989), while Cd2+ fitted Freundlich model (R2 = 0.9689). These parameters inferred the involvement of different combinations of physisorption and chemisorption mechanisms in the adsorption of Pb2+ and Cd2+. However, the thermodynamic parameters indicated the dominance of the physisorption mechanism in the overall exothermic process (∆H = −15.51 and −9.79 kJ·mol−1 for Pb2+ and Cd2+, respectively). Pb2+ and Cd2+ were recovered (≈100%) in 1 M HNO3, and efficient re-adsorption (>80%) was obtained till third reuse cycle. Product was used to treat wastewater and the heavy metals were efficiently removed.